THU0189 Pronostic value of serum bone markers and hand bone densitometry in very early rheumatoid arthritis: preliminary results of the vera study. (1st June 2001) - Vittecoq, O; Daragon, A; Brazier, M; Mejjad, O; Fardellone, P; Krzanowska, K; Boumier, P; Zarnitsky, C; Van, A Phan; Gayet, A; Menard, JF; Le Loët, X
Abstract : Background: Objectives: To study the pronostic value of serum bone markers and hand bone densitometry in very early rheumatoid arthritis (RA). Methods: From a population-based recruitment, 66 patients with very early (median duration: 4.3 months [1 – 6 mo]) peripheral arthritis (swelling > = 2 joints for > 4 weeks) were studied. Patients were steroid and DMARD naive. After a year, patients were classified as RA or non RA. Assessments were performed at entry (T1), after 9 (T2) and 12 (T3) months. Serum bone markers were C telopeptide (ICTP) by ELISA test, free pyridinoline (Pyr) and free deoxypyridinoline (DPyr) by HPLC. Other investigation: hand bone densitometry (DEXA), hands and feet X rays. Prognosis was defined as the progression of radiological damage from T1 to T3 (van der Heijde modified Sharp's method). Results: At T3, 26 patients had radiological progressive disease, and 40 no progressive disease. 50/66 patients fulfilled ACR criteria for RA (75% in non progressive group, 77% in progressive group, NS). At T1, no difference was found between progressive group and non progressive group, excepted for rheumatoid factors more frequent in progressive group (p < 0, 03). Bone mineral density (BMD) of both hands decreased significantly from T1 to T3 in the progressive group (p < 0, 03), whereas it remains unchanged in the non progressive group. Furthermore, ICTP, Pyr and DPyr levels at T1 were negatively correlated to the evolution of hand BMD from T1 to T3 (p < 0, 001, p < 0, 02, and p < 0, 01 respectively). Conclusion: In patients with early RA, a structural bone damage progression after 12 months duration is associated with a decrease of hand BMD. Moreover, this decrease was negatively correlated with levels of serum bone markers at entry. These preliminary results of the VERA study need to be confirmed on a larger population. Study granted by Fondation de la Recherche Médicale and by Pharmacia, France.